Use of a Ureido-Substituted Deoxycytidine Module for DNA Assemblies. (2nd July 2016) - Nakano, Shu-ichi; Oka, Hirohito; Fujii, Masayuki; Sugimoto, Naoki
ABSTRACT: Ureido-substituted cytosine derivatives are promising for constructing self-assembly structures that can be applied to nanotechnology research. However, conventional cytosine modules achieve assembly in organic solvents. In this study, an N-phenylcarbamoyl deoxycytidine nucleoside was incorporated into a C-rich oligonucleotide to achieve self-assembly in aqueous solution. The results show that the capability of the module to form DNA assemblies varied depending on the number of modules incorporated. The deoxycytidine derivative has a potential application in the development of smart materials based on DNA assembly.